The antioxidant activity of Zingiber officinale, Hibiscus sabdariffa, and Caesalpinia sappan combination - Ari Hasna Widyapuspa; Elizabeth Betty Elok Kristiani; Yohanes Martono (Pharmaciana, 2022)
Medicinal plants have been used in traditional treatment since a long time ago by local people in Indonesia. Nowadays, the trend in the consumption of medicinal plants, especially herbal drinks, is increasing. Zingiber officinale, Hibiscus sabdariffa, and Caesalpinia sappan are their main materials of medicinal plants. They were chosen because of their high antioxidant contents. Nevertheless, there is no scientific research on the antioxidant activity of the combination of the three extracts. Therefore, the purpose of this study was to determine the total flavonoid contents and antioxidant activity, as well as to compare the antioxidant enhancement pattern of the combination. Samples were extracted by successive maceration with hexane and ethyl acetate as solvents. Total flavonoids contents were determined through colorimetric analysis and antioxidant activity was determined based on the DPPH method with the IC50 value as a parameter. Total flavonoids of ethyl acetate extract from Z. officinale, H. sabdariffa, and C. sappan were 30.28±0.04; 24.81±0.03; and 24.01±0.04 mg QE/ gram extract, and the IC50 value were 51.36±0.05; 83.37±0.06; and 35±0.04 ppm. Total flavonoid contents of their combination were 22.48±0.05 (0:1:1); 23.88±0.05 (1:1:1); 23.68±0.05 (1:4:1); 22.81±0.05; 28.81±0.04 (4:1:1); 27.55±0.03 (1:1:0); 24.41±0.04 mg QE/ gram extract (1:0:1). Antioxidant activities obtained from the combination were 57.50±0.05 (0:1:1); 52.25±0.06 (1:1:1); 71.50±0.06 (1:4:1); 45.74±0.05 (1:1:4); 54.36±0.05 (4:1:1); 68.97±0.06 (1:1:0); 40.52±0.05 ppm (1:0:1). The strongest antioxidant activity was C. sappan.